IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS PEMBELAJARAN IPAS MI NAHDLATUL ULAMA NGINGAS WARU SIDOARJO - Masfufah, Nindy Arifatul; Mala, Asnal; Arifin, She Fira Azka (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This research aims to determine the implementation of the Problem Based Instruction (PBI) Learning Model in Improving Critical Thinking Ability in Science and Technology Learning at MI Nahdlatul Ulama Ngingas Waru Sidoarjo. This learning model can help teachers improve students' critical thinking skills and self-confidence, both in terms of expressing answers and opinions through problems with the material